Evaluation of fatigue and its correlation with quality of life index, anxiety symptoms, depression and activity of disease in patients with psoriatic arthritis - Carneiro C; Chaves M; Verardino G; Frade AP; Coscarelli PG; Bianchi WA; Ramos-; Carneiro S (Dove Medical Press, 2017)
Claudio Carneiro,1,2 Mario Chaves,2 Gustavo Verardino,2 Ana Paula Frade,3 Pedro Guimaraes Coscarelli,4 Washington Alves Bianchi,5,6 Marcia Ramos-e-Silva,3 Sueli Carneiro2,3 1Health Ministry, 2Sector of Dermatology, School of Medical Sciences and University Hospital, State University of Rio de Janeiro, 3Sector of Dermatology, University Hospital and School of Medicine, Federal University of Rio de Janeiro, 4General Medicine Department, University Hospital and School of Medical Sciences, State University of Rio de Janeiro, 5Sector of Rheumatology, Santa Casa da Misericórdia, 6University Hospital and School of Medical Sciences, State University of Rio de Janeiro, Rio de Janeiro, Brazil Background: Psoriatic arthritis is associated with psychosocial morbidity and decrease in quality of life. Psychiatric comorbidity also plays an important role in the impairment of quality of life and onset of fatigue.Objectives: This study aimed to assess the prevalence of fatigue in psoriatic arthritis patients and to correlate it to quality of life indexes, functional capacity, anxiety, depression and disease activity.Patients and methods: This cross-sectional study was performed on outpatients with psoriatic arthritis. Functional Assessment of Chronic Illness Therapy – Fatigue (FACIT-F; version 4) was used to measure fatigue; 36-Item Short Form Health Survey (SF-36) and Psoriasis Disability Index (PDI) to measure quality of life; Health Assessment Questionnaire (HAQ) to assess functional capacity; Hospital Anxiety and Depression (HAD) scale to measure anxiety and depression symptoms; Psoriasis Area and Severity Index (PASI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Clinical Disease Activity Index (CDAI) to evaluate clinical activity.Results: In all, 101 patients with mean age of 50.77 years were included. The mean PDI score was 8.01; PASI score, 9.88; BASDAI score, 3.59; HAQ score, 0.85; HAD – Anxiety (HAD A) score, 7.39; HAD Depression (HAD D) score, 5.93; FACIT–Fatigue Scale (FACIT-FS) score, 38.3 and CDAI score, 2.65. FACIT-FS was statistically associated with PASI (rs –0.345, p<0.001), PDI (rs –0.299, p<0.002), HAQ (rs –0.460, p<0.001), HAD A (rs –0.306, p=0.002) and HAD D (rs –0.339, p<0.001). The correlations with CDAI and BASDAI were not confirmed. There was statistically significant correlation with all of the domains of SF-36 and FACIT-F (version 4).Conclusion: Prevalence of fatigue was moderate to intense in <25% of patients with psoriatic arthritis. Fatigue seems to be more related to the emotional and social aspects of the disease than to joint inflammatory aspects, confirming that the disease’s visibility is the most disturbing aspect for the patient and that “skin pain” is more intense than the joint pain. Keywords: psoriasis, arthritis, fatigue, quality of life, anxiety, depression, questionnaires